Maturação fisiológica e desempenho de sementes no armazenamento de Quillaja brasiliensis (A. St. Hil. & Tul.) Mart. (Quillajaceae) para a região de Bagé - RS. - Cantos, Alexandra Alves (2009)
The aeration of soybean seeds with cold air has been used in several decades, and its benefits in maintaining quality are well known. Recently, the aeration with cold air produced by cooling units is gaining acceptance, particularly in regions where the aeration with cold ambient air is not possible. The chill of soybean seeds with naturally or artificially produced cold air is a very important step for maintaining the physiological quality of seeds. Despite its benefits within the process of seed production, the potential and flexibility of the cold treatment of seed has not been fully exploited by seed makers. The objective of this work is evaluate the effects of aeration with air conditioning on physiological quality of soybean seeds after a period of conventional storage. The study was conducted at COODETEC in Cascavel - Paraná, with the cultivar CD 212RR. In this work, a portion of 73 bags was cooled for 53 minutes with cold air inflation to reach 15 ° C using a cooling unit. Another portion of 67 bags were stored without the cooling process. Both portions were stored for eight months in two separate blocks, but under the same environmental conditions. Seed samples of the two portions were taken every two months and sent to the COODETEC Laboratory of Seed Analysis for germination tests using the following methods: paper test, sand germination, accelerated aging germination and the first count germination. The analysis of variance showed significant differences between the treatments. In the standard germination test applied after eight months of storage, the cold-treated seeds showed only three percentage points reduction in germination, down from 88% to 85%. In the samples without cold treatment, the germination dropped 28 points before bagging , down from 88% to 60%. It demonstrates the benefits of cold treatment of soybean seeds, in order to maintaining the physiological quality of seeds.